EXTRALINGUISTIC ISSUES IN CROSS-CULTURAL COMMUNICATION: SOCIAL ROLES IN DIFFERENT CULTURES, STEREOTYPES, IMAGES, SYMBOLS - Otabekova Hulkaroy; G’aniyevaTohira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
An rising number of businesses are expanding internationally in the dynamic business environment of today. It can be particularly difficult to communicate effectively with persons from various cultures. Business firms' behavior in markets with multiple cultural reflections is influenced by their cultural awareness. It is widely acknowledged that cultural differences impose imperceptible obstacles on cross-border commercial communications. One of the most important abilities for businesses to develop in order to have a competitive advantage in international business is the ability to understand cultural differences.